Pengaruh Intervensi Akupunktur Sebagai Induksi Alami Terhadap Lamanya Persalinan Kala I - Yoppie William Gerungan; Mellisa Mellisa (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This research is a quantitative type with a pre-experimental design in the form of Intact-Group Comparison to examine the effect of acupuncture intervention as a natural induction on the duration of the first stage of labour. This study was conducted on the acupuncture intervention treatment group and the control group that did not receive acupuncture intervention as a natural induction. The sampling technique used was purposive sampling according to the inclusion and exclusion criteria. Each group consisted of 15 first stage births at the R Sukabumi Midwife Clinic so that the total sample was 30 respondents. Intervention was carried out by performing acupuncture at points LI4, SP6, LR3, BL67 and ST36 when it was found that they had entered the active phase of the first stage of labour. The research instrument used a partograph observation sheet to see the length of time in the first stage of labor with an analytical test using the Mann-Whitney test with a significance level of 95% or α = 0.05. The results of the analysis showed that before acupuncture intervention as a natural induction, 73.3% of mothers in labor experienced the first stage for ≥ 6 hours, but after acupuncture intervention as a natural induction, 80% of mothers in labor experienced an accelerated first stage to <6 hours. This means that there is a significant relationship to the effect of acupuncture intervention as a natural induction on the duration of the first stage of labor (Sig. (2 tailed) 0.000 < α = 0.05). Keywords: Acupuncture, natural induction, length of labour, stage I Abstrak Penelitian ini berjenis kuantitatif dengan pre-experimental design bentuk Intact-Group Comparison untuk menguji pengaruh intervensi akupunktur sebagai induksi alami terhadap lama persalianan Kala I. Studi ini dilakukan terhadap kelompok perlakuan intervensi akupunktur dan kelompok kontrol yang tidak mendapat intervensi akupunktur sebagai induksi alami. Teknik sampling yang digunakan yaitu purposive sampling sesuai kriteria inklusi dan eksklusi. Masing-masing kelompok terdiri dari 15 inpartu kala I di Klinik Bidan R Sukabumi sehingga total sampel adalah 30 responden. Intervensi dilakukan dengan melakukan akupunktur pada titik LI4, SP6, LR3, BL67 dan ST36 ketika diketahui sudah masuk ke fase aktif kala I persalinan. Instrumen penelitian menggunakan lembar observasi partograf untuk melihat lamanya waktu persalinan kala I dengan uji analisis menggunakan uji Mann-Whitney dengan taraf signifikansi sebesar 95% atau α =0,05. Hasil analisis menunjukan bahwa sebelum dilakukan intervensi akupunktur sebagai induksi alami 73,3% ibu inpartu mengalami kala 1 selama ≥ 6 jam namun setelah dilakukan intervensi akupunktur sebagai induksi alami 80% ibu inpartu mengalami percepatan kala 1 menjadi < 6 jam. Artinya ada hubungan yang signifikan untuk pengaruh intervensi akupunktur sebagai induksi alami terhadap lamanya persalinan Kala I (Sig. (2 tailed) 0,000 < α =0,05). Kata kunci: Akupunktur, induksi alami, lama persalinan, kala I